Storytelling as a tool for creating a brand image - Głowacz, Anna (Linguistic creativity in marketing, 2022)
The article presents the essence of storytelling and the possibilities of using it in creating a brand image. The article consists of three elements. The first part of the article presents the concept of a brand and its image, as well as the principles and stages of creating a brand image. The second part explains the essence of storytelling and the types of tools used in storytelling. Archetypes are presented, which are an important element in creating a brand image. The last part of the work presents the creation of a brand image using storytelling on the example of the DocMorris Christmas campaign.